2010
DOI: 10.1016/j.visres.2010.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A metanalysis of the effect of the Müller-Lyer illusion on saccadic eye movements: No general support for a dissociation of perception and oculomotor action

Abstract: Milner and Goodale's (1995) proposal of a functional division of labor between vision-for-perception and vision-for-action is supported by neuropsychological, brain-imaging, and psychophysical evidence. However, there remains considerable debate as to whether, as their proposal would predict, the effect of contextual illusions on vision-for-action can be dissociated from that on vision-for-perception. Meta-analytical efforts examining the effect of the Müller-Lyer (ML) illusion on pointing (Bruno, Bernardis, &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 63 publications
6
22
0
Order By: Relevance
“…However, there was some influence of the illusion on pointing constant error at the end of movement execution, consistent with past research (for review, see Bruno et al, 2010). Given the similarity in IL and MT responses to physical and illusory size manipulation observed in pointing and saccades, we were able to compare the findings from these two effectors directly, and examine the potential for shared underlying mechanisms.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, there was some influence of the illusion on pointing constant error at the end of movement execution, consistent with past research (for review, see Bruno et al, 2010). Given the similarity in IL and MT responses to physical and illusory size manipulation observed in pointing and saccades, we were able to compare the findings from these two effectors directly, and examine the potential for shared underlying mechanisms.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, others have shown that measures other than grasp aperture are susceptible to visual illusions, such as movement amplitude (de Grave, Brenner, & Smeets, 2004), or how the object is lifted or gripped (Brenner & Smeets, 1996; Jackson & Shaw, 2000). Several studies have shown that both saccadic and pointing movements are susceptible to the Müller-Lyer illusion, such that when lines are perceived as longer, movements to their perceived endpoints have longer amplitudes (for review, see Bruno et al, 2010). Thus, it is argued that illusory perception does have an effect on aspects of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such dissociation is controversial and might be an experimental artifact. Indeed, without any visual feedback, hand and eye movements (and consequently the “vision for action”) can also be affected by the illusion (Bruno and Franz, 2009; Bruno et al, 2010). Similarly, in illusions where the perceived depth is different from the actual depth, the vergence movements are sometimes subject to the depth cues of the physical world (Wismeijer et al, 2008), and sometimes to the illusory percept (Sheliga and Miles, 2003).…”
Section: Improving Visual Perception and Awarenessmentioning
confidence: 99%
“…Visual illusions have been extensively used to examine dissociations between vision for perception and vision for action (for meta-analyses and reviews, see Bruno, Bernardis, & Gentilucci, 2008;Bruno & Franz, 2009;Bruno, Knox, de Grave, 2010;Milner & Goodale, 2008). Aglioti, DeSouza, and Goodale (1995) were the first to report that when participants were asked to grasp the inner circle of an Ebbinghaus illusion configuration, their actions (more specifically, their maximum grip apertures) were not affected by the illusion, whereas verbal judgments of the size of the inner circle showed the typical illusion effects (for similar results, see Haffenden & Goodale, 1998).…”
Section: Introductionmentioning
confidence: 99%